Behavioral Specialization During the Neolithic—An Evolutionary Model - Vásárhelyi, Zsóka; Scheuring, István (Frontiers in Sociology, 2018)
The emergence of agriculture and complex societies during the Near Eastern Neolithic opened a new era in human evolution. Food production seriously affected the ecological environment, and societies answered this challenge with large-scale division of labor and specialization. In this paper we study this transition with an individual based model. Our model captures the connections between the appearance of agriculture, the social division of labor, and human behavioral diversity. Our two main settings are different habitats: in the pre-Neolithic habitat, resources fluctuated in time and there was no large-scale food storage. In the Neolithic habitat active food production resulted in economic surplus. We consider a sexually reproducing social group, in which individuals solve different tasks for survival. We assume that the task-solving effectiveness has a partial genetic basis but also improves with experience and learning. Since different tasks can require somewhat different skills, we assume trade-offs between genetic propensities for different tasks. Individuals are born with inherited task-choice strategies that they can improve by imitating more successful peers. We show that for the Neolithic case, both phenotypic specialization (task choice strategy) and the emergence of genetic polymorphism are possible, as long as scarcer goods are more valuable. As the number of tasks increases, specialization can evolve only in very large groups. Although phenotypic specialization often emerges in our model, the emergence of genetic polymorphism requires strong assortativity during both imitation and mate choice. In sum, our model shows that if an economic surplus becomes available, behavioral specialization and large-scale division of labor are likely to appear. Thus, our model can help understanding certain aspects of the Neolithic transition, and may have implications for the present genetic polymorphism, too.